Households’ behavior and social-environmental aspects of using bag dustbin for waste recovery in Tehran - Amanidaz, Nazak (J Environ Health Sci Eng, 2019)
The suitable dustbin can cause a significant increase in household participation in separated dry waste at production source and recycling rate. This study was conducted on 100 households in Tehran for two weeks for households’ wastes without any intervention. After two weeks, the tough-flexible bag dustbins were delivered to the families. At the next stage, by analysing the separated dry wastes by households, comparing the cost of new bag dustbin with plastic garbage bags, and completing some questionnaires, it was concluded that about 92% of households believed that waste bag dustbin was much more accessible and hygienic. The use of plastic garbage bags was decreased an average by 2, after using new bag dustbins. Moreover, the use of bag dustbins has more cost-effectiveness rather than plastic bags (about 54%). Before and after the intervention, the source separation and recovery rate was 0.19 and 0.18, respectively. The amount of wet waste in the waste bag dustbin was decreased to 62.26% after the intervention. The decrease of wet waste in the separated dry waste enhanced the quality of recycled materials.